Determinasi Jumlah Bakteri Porphyromonas Gingivalis ATCC 33277 pada Saliva Anak Stunting - Nadhifah Salsabila; Nila Kasuma; Eti Yerizel (Universitas Sam Ratulangi, 2024)
Abstract: Nutrition affects the immune system and the development of oral health, including periodontal tissue health. Stunted children experience decreased salivary flow rate causing the growth of microorganisms that cause periodontal disease. Porphyromonas gingivalis is referred to one of the keystone pathogens in the development of periodontal disease. This study aimed to identify the number of Porphyromonas gingivalis ATCC 33277 bacteria in stunted child saliva. This was a descriptive study with a cross sectional design. Prior to collection, subjects were instructed to rinse their mouth for 30 seconds using distilled water, saliva was collected with draining method, then 2 mL of saliva was taken, and DNA was isolated from Porphyromonas gingivalis ATCC 33277. DNA amplification and DNA calculation of Porphyromonas gingivalis ATCC 33277 were performed by using Real-time PCR. The results obtained 23 stunted children age 6-12 years as subjects. The average number of Porphyromonas gingivalis ATCC 33277 bacteria in stunting child saliva was 230.8 x 106 ± 320.1 x 106 CFU/ml. In conclusion, the number of Porphyromonas gingivalis ATCC 33277 is higher in stunted children saliva than in normal child saliva. Keywords: stunted children; Porphyromonas gingivalis ATCC 33277 bacteria; periodontal diseases Abstrak: Gizi memengaruhi sistem pertahanan dan perkembangan kesehatan rongga mulut termasuk kesehatan jaringan periodontal. Anak stunting mengalami penurunan laju alir saliva yang menyebabkan pertumbuhan mikroorganisme penyebab penyakit periodontal, antara lain Porphyromonas gingivalis sebagai salah satu keystone pathogens dalam perkembangan penyakit periodontal. Penelitian ini bertujuan untuk menentukan jumlah bakteri Porphyromonas gingivalis ATCC 33277 pada saliva anak stunting. Jenis penelitian ialah deskriptif dengan desain potong lintang. Sebelum pengambilan saliva, subjek diinstruksikan berkumur selama 30 detik menggunakan akuades. Pengambilan saliva dengan metode draining selama 10 menit, saliva terkumpul sebanyak 2 mL, dan dilakukan isolasi DNA bakteri Porphyromonas gingivalis ATCC 33277. Amplifikasi DNA dan perhitungan jumlah DNA bakteri Porphyromonas gingivalis ATCC 33277 dilakukan menggunakan Real-time PCR. Hasil penelitian mendapatkan 23 anak stunting dengan usia 6-12 tahun. Rerata jumlah bakteri Porphyromonas gingivalis ATCC 33277 pada saliva anak stunting 230,8x106±320,1x106 CFU/ml yang lebih tinggi daripada anak sehat yaitu 180,8x106±201,8x106 CFU/mL Simpulan penelitian ini ialah rerata jumlah bakteri Porphyromonas gingivalis ATCC 33277 pada saliva anak stunting lebih tinggi daripada saliva anak normal. Kata kunci: anak stunting; bakteri Porphyromonas gingivalis ATCC 33277; penyakit periodontal